How would you add these two fractions?

3a/(a-2b) + 6b/(2b-a)

3a/(a-2b) + 6b/(2b-a)

3a/(a-2b) + 6b/(2b-a)

= 3a/(a - 2b) + 6b/(-a + 2b) {flipped the 2nd denominator}

=3a/(a - 2b) - 6b/(a - 2b) {multiplied top and bottom of 2nd fraction by -1}

notice, you now have a common denominator

3a - 6b

--------{combined like terms in numerators}

a - 2b

3(a - 2b)

------------ {factored 3 out of top}

a - 2b

= 3 {cancelled (a - 2b) on top and bottom}

- Algebra House

= 3a/(a - 2b) + 6b/(-a + 2b) {flipped the 2nd denominator}

=3a/(a - 2b) - 6b/(a - 2b) {multiplied top and bottom of 2nd fraction by -1}

notice, you now have a common denominator

3a - 6b

--------{combined like terms in numerators}

a - 2b

3(a - 2b)

------------ {factored 3 out of top}

a - 2b

= 3 {cancelled (a - 2b) on top and bottom}

- Algebra House